Sign in
Please select an account to continue using cracku.in
↓ →
$$(1 + x + x^2)^n = \sum_{k=0}^{2n} a_kx^k \Rightarrow \sum_{k=0}^{n} a_{2k}$$
$$\frac{1}{2}(3^{2n} + 1)$$
$$\frac{1}{2}(3^{n} - 1)$$
$$\frac{1}{2}(3^{n} + 1)$$
$$\frac{1}{2}(3^{2n} - 1)$$
Create a FREE account and get:
Terms of Service
CAT Formulas PDFCAT Syllabus PDFCAT Study Plan PDFCracku Brochure
Day-wise Structured & Planned Preparation Guide
By proceeding you agree to create your account
Free CAT Schedule PDF will be sent to your email address soon !!!